(دور العدالة التنظيمية بأبعادها المختلفة في تعزيز الرضا الوظيفي) (Comprehensive Journal of Science, 2025)
The study aimed to identify the impact of organizational justice, with its dimensions (distributive, procedural, and transactional), on enhancing job satisfaction among employees of the North African Bank - Abu Salim Branch. The study relied on a descriptive-analytical approach using a questionnaire distributed to a sample of (35) employees. The results showed that the level of organizational justice was average, with an arithmetic mean of (2.61), with distributive justice being low, while procedural and transactional justice were at an average level. The results also indicated that the level of job satisfaction was low (2.25). The research hypotheses confirmed the existence of a positive and statistically significant effect between organizational justice and job satisfaction. The study concluded that distributive justice has the greatest impact on job satisfaction compared to other dimensions. The study recommended the need to enhance distributive, procedural, and transactional justice by improving wage and incentive systems, developing mechanisms for participation in decision-making, and supporting effective communication between management and employees.
Keywords: Organizational Justice - Job Satisfaction - North African Bank